Identification of an allergenic calmodulin from Amaranthus palmeri pollen. (April 2021) - Gómez-Esquivel, Mónica Luz; Guidos-Fogelbach, Guillermo Arturo; Rojo-Gutiérrez, María Isabel; Mellado-Abrego, Jaime; Bermejo-Guevara, Mario Alberto; Castillo-Narváez, Gloria; Velázquez-Sámano, Guillermo; Velasco-Medina, Andrea Aida; Moya-Almonte, Margaret Gissett; Vallejos-Pereira, Carla Marcela; López-Hidalgo, Marisol; Godínez-Victoria, Marycarmen; et al.
Highlights: The calmodulins are small calcium-binding proteins found in all eukaryotes. Calcium-binding allergens are clinically relevant antigens. Amaranthus palmeri pollen extracts contain a calmodulin. The calmodulin can sensitize patients allergic to Amaranthus palmeri pollen. Abstract: Introduction: Pollens are an important source of allergens that trigger rhinitis or asthma. The allergenic extracts of pollens used to diagnose and treat allergies contain different allergenic antigens. Isolated allergenic proteins are employed in in vitro assays, skin tests and allergenic-specific immunotherapy. Calcium-binding allergens are clinically relevant antigens, and their allergenicity can be affected by Ca 2+ binding. In this work, a calmodulin was identified as an allergen from Amaranthus palmeri pollen, an important source of pollinosis in Europe, Asia and North America. Materials and methods: Allergenic calmodulin from A. palmeri pollen was isolated by size-exclusion chromatography and reverse-phase chromatography and identified by mass spectrometry. Sensitization to isolated calmodulin was evaluated by skin prick tests in patients with allergy to A. palmeri pollen. Results: Size-exclusion chromatography yielded two fractions that were recognized by the IgE of patients allergic to A. palmeri pollen. Mass spectrometry analysis of the fractions from reverse-phase chromatography showed peptide sequences that identified a calmodulin. Skin prick tests showed that the isolated calmodulin was recognized by 56% of patients allergic to A. palmeri pollen. Conclusion: A. palmeri pollen calmodulin could be a clinically relevant allergen in patients sensitized to this source.